Returning to secondary education after early school dropouts: music as a reconnecting factor - Picazo-Gutiérrez, Marina; Gil de Gálvez, José Manuel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The general objective of this research has been based on analyzing and understanding part of the results of the main research that focus on the subject himself as the main actor of his story. In this sense, the role that music plays within the non-formal and informal learning contexts is investigated as a way to create empowering relationships of those students in a situation of failure and/or school dropout, in order to seek positive measures of reengagement with the educational system from their experiences within the context of learning outside the curricular world.